O regime dos acordos internacionais de investimentos e a capacidade regulatória dos estados: estudo de caso sobre o Energy Charter Treaty - Casnati, Gabriel (2023)
This research aims to investigate the tensions between the international investment agreements (IIAs) regime, and the States' regulatory capacity and space for elaborating public policies, pointing out asymmetries between the global north and south. To that end, the work carried out a literature review, and the collection and systematization of data from cases registered in international arbitration through the Investor-State Dispute Settlement (ISDS) system. The work is based on the theoretical findings that global governance has become progressively privatized and fragmented, following the neoliberal frameworks consolidated in the 1990s. This process states the strengthening of corporate power in the face of the dilution of state sovereignty, as well as the overlapping of distinct and incompatible legal orders, with commercial law operated by private actors imposing itself over international public law and multilaterally agreed global goals. From this frame, the research presents and deconstructs the arguments that support the investment regime, and advances by demonstrating, in the case study, how the Energy Charter Treaty has restricted the space of its member countries for the elaboration of public policies on energy and climate, both in the fossil fuels sector and in the renewable energy sector. Based on the results obtained, it is possible to establish a direct relationship between the consolidation of the international investment agreements regime and the restriction of regulatory capacity and legislative autonomy of states, at least in the energy field. The research is expected to encourage further investigations that analyze the relationship of the international investment agreements regime with other areas of public policies, especially in human rights, such as the protection of territories, labor rights, and access to health, education, and sanitation